Hubungan Tingkat Pengetahuan dan Persepsi dengan Stigma Masyarakat terhadap ODHA di Desa Naras I - Yulia M Nur; Mona Yolanda; Zul Adhani J.S Can (Jurnal Akademika Baiturrahim Jambi, 2022)
Cases of HIV/AIDS transmission in Pariaman City fluctuated, meaning that in the span of 2018 to 2020 there was an increase and decrease, as well as the number of cases of HIV/AIDS transmission in Naras 1 Village which each year increased. The purpose of this study was to determine the relationship between the level of knowledge and perception with community stigma against PLWHA in Naras I Village, North Pariaman District, Pariaman City. The population in this study is all people aged between 15 years to 49 years, totaling 2,532 residents in Naras I Village, and a total sample of 100 respondents. Data were collected using a questionnaire and analyzed using the SPSS16.0 program. The results of this study are the results of the Chi-Square test of 0.048 (p-value <0.05) meaning that there is a relationship between the level of knowledge and the stigma of society towards PLWHA and the Chi-Square test of 0.174 (p-value > 0.05) meaning that there is no relationship level of knowledge with community stigma against PLWHA. The conclusions in this study are; 1) Most of the respondents in this study were male, aged between 21 and 30 years old, had other occupations such as (IRT, laborers, farmers, and others). 2) There is no relationship between the level of knowledge and the community's stigma towards PLWHA in Naras I Village.